Effect of Mitomycin C on recurrence of plantar fibromas. Issue 9 (23rd May 2018) - Amer, Kamil M.; Mohamed, Sana; Amer, Rami; Chaudhry, Ahmed; Winters, Brian; Abraham, John A.
ABSTRACT: Although certainly not the first line treatment for plantar fibromas, surgical resection is a treatment option for some patients with have failed exhaustive non‐surgical treatment. The use of topical Mitomycin C has been recently shown to reduce the recurrence rate of other fibrous lesions. The purpose of this study was to determine the impact of topical application of Mitomycin C on recurrence rate of plantar fibromas. A retrospective analysis was done from a prospectively gathered database with a total 50 consecutive patients over a 16‐month study period. The control group ( n  = 29) consisted of patients who underwent only surgical resection, while the study group ( n  = 21) consisted of patients who underwent surgical resection with adjuvant therapy using Mitomycin C. The primary endpoint was local recurrence after the procedure. Secondary end points included complications and toxicity associated with this medication. No patients were lost to follow up. Of the 29 patients in the control group, there were 17 patients (17/29, 58.6%) had recurrence of the plantar fibroma at a mean follow‐up of 9.1 months. In contrast, in the experimental study group, all patients were free from local recurrence. No complications or side effects were associated with Mitomycin C use. The results demonstrate that the topical application of Mitomycin C to the tumor bed after surgical resection of plantar fibromas reduced the recurrence rate. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2554–2561, 2018.